Retorika pada Akun Instagram @Jerome Polin dalam Membangun Citra Diri Edukataif dan Inspiratif - Alviana Heranamawanti Irawan; Desma Yuliadi Saputra; Rina Andriani (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2026)
This study aims to analyze rhetoric on the social media account @JeromePolin in constructing an educational and inspirational self-image. The study employed a qualitative approach with a descriptive method. The data consisted of video uploads, captions, and visual communication on the @JeromePolin account selected purposively. Data collection techniques included observation and documentation, while data analysis used Aristotle’s rhetorical theory consisting of ethos, pathos, and logos. The findings show that the ethos element is reflected through academic credibility, consistency in educational content, and an authentic communication style that strengthens audience trust. The pathos element appears through personal narratives, humor, and motivational messages that create emotional closeness and engagement with audiences, making the communication more relatable and persuasive. Meanwhile, the logos element is demonstrated through logical, systematic, and understandable educational content delivery that helps audiences easily grasp complex information. The integration of these rhetorical elements forms an effective persuasive communication strategy in constructing Jerome Polin’s self-image as an educational and inspirational figure on social media. Overall, the combination of ethos, pathos, and logos shows how digital communication can shape public perception and reinforce the role of social media influencers in promoting educational values in contemporary society.